2017
DOI: 10.5194/amt-10-4235-2017
|View full text |Cite
|
Sign up to set email alerts
|

Combined neural network/Phillips–Tikhonov approach to aerosol retrievals over land from the NASA Research Scanning Polarimeter

Abstract: Abstract. In this paper, an algorithm for the retrieval of aerosol and land surface properties from airborne spectropolarimetric measurements -combining neural networks and an iterative scheme based on Phillips-Tikhonov regularization -is described. The algorithm -which is an extension of a scheme previously designed for ground-based retrievalsis applied to measurements from the Research Scanning Polarimeter (RSP) on board the NASA ER-2 aircraft. A neural network, trained on a large data set of synthetic measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…POLDER-3 data have been used for a wide range of applications, including aerosol retrievals (Dubovik et al, 2011;Hasekamp et al, 2011;Waquet et al, 2013), retrieval of cloud properties (Riedi et al, 2010;Parol et al, 2013;van Diedenhoven et al, 2014b;Desmons et al, 2017), water vapour retrievals , estimation of surface properties (Bréon and Maignan, 2017) and validation of surface reflection models (Kokhanovsky and Bréon, 2012).…”
Section: The Polder-3 Instrumentmentioning
confidence: 99%
“…POLDER-3 data have been used for a wide range of applications, including aerosol retrievals (Dubovik et al, 2011;Hasekamp et al, 2011;Waquet et al, 2013), retrieval of cloud properties (Riedi et al, 2010;Parol et al, 2013;van Diedenhoven et al, 2014b;Desmons et al, 2017), water vapour retrievals , estimation of surface properties (Bréon and Maignan, 2017) and validation of surface reflection models (Kokhanovsky and Bréon, 2012).…”
Section: The Polder-3 Instrumentmentioning
confidence: 99%
“…Figure 2 shows a schematic of the used method and detailed descriptions of the method can be found in the textbooks of the subject (e.g., Buduma and Locascio, 2017;Duda et al, 2012). In general, the NNs are built by stacking interconnected layers of atomic units, or neurons.…”
Section: Discussionmentioning
confidence: 99%
“…There are as many learning methods as there are NN topologies; however, they can be sorted in a few categories. For instance, the learning method may require a labeled training set, falling into the supervised learning (SL) category (Duda et al, 2012;Amari, 1998), or it may learn by itself without an already classified set, in which case the method is referred to as unsupervised learning (UL) (Le, 2013;Radford et al, 2016). Another relevant classification of the learning methods is the depth of the NN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hasekamp et al (2011), while looking at multi-angular measurements, considered also the case of adding polarization to I-only retrievals and found improved agreement with ground-based (AERONET) data. Di Noia et al (2017) found that use of a neural network to provide an initial guess for an iterative algorithm led to a decrease in processing time and an increase in the number of converged retrievals. And neural networks have been used to directly retrieve products, e.g., ozone column amounts from ground-based irradiance measurements (Fan et al, 2014) or satellite water-leaving radiances (Fan et al, 2017), and have also been used with optimal estimation, e.g., retrieval of snow products from ground-based total radiance measurements (Tanikawa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%